EPIDEMIOLOGICAL INVESTIGATION OF DIROFILARIA IMMITIS IN MOSQUITOES FROM SAMARKAND REGION, UZBEKISTAN: PRELIMINARY RESULTS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Dirofilaria immitis, commonly known as heartworm, poses a substantial threat to canines in the Samarkand region, Uzbekistan. This study aims to comprehensively investigate the prevalence and transmission dynamics of Dirofilaria immitis, considering the distinctive geographical and climatic factors influencing disease spread. A cross-sectional survey conducted from January 2022 to December 2023, involved the Knott's test, the presence of D. immitis microfilariae was assessed. Simultaneously, 4828 female mosquitoes were sampled in June, July and September 2023 to investigate their potential role as vectors. A total of 41 (25.7%) dogs tested positive for D. immitis microfilariae. District-wise analysis highlighted significantly higher infection rates in Urgut 10 (55.5%), Jomboy 6 (42.8%), and Payariq 11 (42.3%) districts. Concurrently, an infection rate of 4.9% was observed in 237 mosquitoes, with the Jomboy mosquitoes having the highest infection rate of 130 (54.8%). The prevalence of D. immitis larvae in mosquitoes is notably elevated, ranging from 3.8% to 10.2% in the studied areas of the Samarkand region. The intensity of infestation varied from 16-26 larvae in Culex pipiens and 10-16 larvae in Anopheles maculipennis.